2005
DOI: 10.1071/bt04033
|View full text |Cite
|
Sign up to set email alerts
|

Dendroclimatological potential of the Australian red cedar

Abstract: Abstract. We examined Toona ciliata M.Roemer (Australian red cedar) for its potential to deliver annually resolved tree-ring proxy data. Such proxies are valuable and sought-after sources for reconstructing climate beyond instrumental records, especially in Australia. T. ciliata was chosen because it is one of the few deciduous tree species in Australia experiencing a seasonally dormant period of the cambium. This was confirmed by a preliminary treering analysis which revealed distinct growth rings. Because of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…The presence of thick-walled and radially flattened latewood fibers versus thin-walled earlywood was the most common growth ring boundary, commonly found in a great number of tropical species (Worbes 1989;Callado et al 2001;Lisi et al 2008). ''False'' rings as observed in some studied species (especially Inga edulis, I. marginata and Myrsine coriacea) are a ring anomaly relatively frequent in species growing in weakly seasonal tropical regions (Heinrich and Banks 2005). They are explained by temporary growth limitation in a stressful period caused, for example, by low temperatures, flooding (Speer 2010), drought stress (Priya and Bhat 1999;Wimmer et al 2000), and by abrupt variation from dry to wet period (Masiokas and Villalba 2004).…”
Section: Discussionmentioning
confidence: 97%
“…The presence of thick-walled and radially flattened latewood fibers versus thin-walled earlywood was the most common growth ring boundary, commonly found in a great number of tropical species (Worbes 1989;Callado et al 2001;Lisi et al 2008). ''False'' rings as observed in some studied species (especially Inga edulis, I. marginata and Myrsine coriacea) are a ring anomaly relatively frequent in species growing in weakly seasonal tropical regions (Heinrich and Banks 2005). They are explained by temporary growth limitation in a stressful period caused, for example, by low temperatures, flooding (Speer 2010), drought stress (Priya and Bhat 1999;Wimmer et al 2000), and by abrupt variation from dry to wet period (Masiokas and Villalba 2004).…”
Section: Discussionmentioning
confidence: 97%
“…In northern Argentina, Toona ciliata (Australian red cedar) has been identified as a suitable species for production of high quality and economically valuable timber. Because of its value for veneer and lumber products (Bahadur, 1988;Edmonds, 1995;Heinrich and Banks, 2005), T. ciliata cultivation is expanding rapidly. T. ciliata has similar wood characteristics and uses to those of the highly sought-after north-eastern Argentina native, Cedrela odorata, and its cultivation may reduce the harvesting pressure on C. odorata in native forests (Mangialavori et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…For the three studied species showing distinct growth rings, more research is needed to clarify the annual nature of the observed rings. The study period should include more than 1 year and trees of different sizes should be included in order to be able to assess ontogenetic effects on anatomy and distinctness of growth rings (Brienen and Zuidema 2005;Heinrich and Banks 2005;Esper et al 2008). For now, we advice that tree rings in mangroves should be handled on a caseby-case basis and should only be used for age or growth rate estimations after at least a preliminary investigation of the annual nature of the wood anatomically definable zones that can be seen in the wood.…”
Section: Heritiera Littoralismentioning
confidence: 99%